A Phytochemical Perspective on Plant Defense Against Nematodes - Desmedt, Willem; Mangelinckx, Sven; Kyndt, Tina; Vanholme, Bartel (Frontiers in Plant Science, 2020)
Plant-parasitic nematodes are among the most devastating plant pests. To defend themselves against nematode attack, plants possess sophisticated multi-layered immune systems involving various mechanisms. One such mechanism is the production of small molecules with anti-nematode properties, either constitutively or induced upon nematode infection. This review provides an overview of known anti-nematode phytochemicals, of strategies for their identification and of ways in which knowledge of these metabolites could advance agriculture and crop protection.